2016
DOI: 10.1136/bmjopen-2016-011341
|View full text |Cite
|
Sign up to set email alerts
|

Patient and family satisfaction levels in the intensive care unit after elective cardiac surgery: study protocol for a randomised controlled trial of a preoperative patient education intervention

Abstract: IntroductionPatients and their families are understandably anxious about the risk of complications and unfamiliar experiences following cardiac surgery. Providing information about postoperative care in the intensive care unit (ICU) to patients and families may lead to lower anxiety levels, and increased satisfaction with healthcare. The objectives of this study are to evaluate the effectiveness of preoperative patient education provided for patients undergoing elective cardiac surgery.Methods and analysis100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 42 publications
1
33
0
2
Order By: Relevance
“…Furthermore, they expected to have sufficient time to ask the surgeon some questions and receive satisfactory answers. Good communication between the patient's family and health professionals by directly explaining the status of the surgical progress can reduce the family's anxiety and increase their satisfaction with nursing (Balogh-Mitchell, 2012;Lai et al, 2016;Oberoi et al, 2016;Yang, 2010;Y. A. Yun, 2012).…”
Section: Sage Openmentioning
confidence: 99%
“…Furthermore, they expected to have sufficient time to ask the surgeon some questions and receive satisfactory answers. Good communication between the patient's family and health professionals by directly explaining the status of the surgical progress can reduce the family's anxiety and increase their satisfaction with nursing (Balogh-Mitchell, 2012;Lai et al, 2016;Oberoi et al, 2016;Yang, 2010;Y. A. Yun, 2012).…”
Section: Sage Openmentioning
confidence: 99%
“…Many studies have shown that satisfaction with care can be influenced by factors relating to a patient’s demographic and clinical characteristics,32 33 such as age,34 insurance status12 and mental health 35. Other components of satisfaction have been tied to accessibility of care, communication and decision-making, emotional support, coordination of care, pain management, and psychological health; however, an agreed on consensus has yet to be reached 3–5 15 32 36–39. We observed that satisfaction was related to some elements of a patient’s clinical status, as well as communication of information, availability and coordination of care, and symptom management.…”
Section: Discussionmentioning
confidence: 74%
“…The provision of patient-centred and family-centred medical care is well established in the published literature, with multiple studies highlighting the need for attention to experiences of both the patientand their family members 1–4. Particularly in older adult patients and their families, the need for satisfaction with communication and the management surrounding end-of-life treatment strategies is evident 5 6.…”
Section: Introductionmentioning
confidence: 99%
“…Some foreign scholars have applied the non-drug psychological intervention nursing method to relieve anxiety after cardiac surgery. Lai et al 30suggested that patients and their families are unfamiliar with cardiac surgery and its complications, which leads to postoperative anxiety. Providing postoperative nursing information to patients and their families could effectively reduce anxiety.…”
Section: Discussionmentioning
confidence: 99%